Rancang Bangun Mesin Pencampur Bijih Plastik Berkapasitas 20 Gram: design and construction - Setiyawan, Bambang; Ardita, Eduardo (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2024)
In the process of creating various types of plastic, several tools are required to support the development process. In this regard, Politeknik Industri ATMI has attempted to develop a supporting tool for mixing plastic ore. The objective of this research is to design, build, and test an efficient and economical mixing machine for processing plastic ore on a small scale. To create this tool, the author used observation and design realization methods. After a lengthy process, a plastic ore mixing machine with a capacity of 20 grams was produced. This paper discusses the plastic ore mixing machine designed for use in testing laboratories. This mixing machine is a device used to process plastic ore into new types. In this study, the author developed a plastic ore mixing machine with a volume capacity of 20 grams. This machine is used to combine two or more types of plastic ore, aiming to produce high-quality plastic. To achieve this, the machine was developed using two mixing shafts and a melting system with heating elements. Additionally, the mixing process chamber was designed with two compartments, corresponding to the positions of the mixing shafts. This design is expected to maximize the mixing process of each type of plastic, resulting in a homogeneous plastic product.